Using Simulated Video Analysis to Promote Special Education Teacher Candidates' Professional Knowledge and Reflective Ability. (November 2022) - Nagro, Sarah A.; Monnin, Kevin
The purpose of this study was to investigate the potential of simulated video analysis where candidates with differing educational backgrounds taught their peers prior to engaging in an authentic field experience. Teacher candidates' special education professional knowledge, reflective ability, and instructional skills were tracked to understand if outcomes differed based on teacher candidates' previous teaching experience or progress toward licensure. All 37 candidates participated in three simulated video analysis sessions by recording their instruction during role-play with peers, reviewing their video independently in class, and completing a reflection matrix. Finally, candidates completed a culminating field experience project with a P-12 focus student. Results indicated significant improvements in both special education professional knowledge and reflective ability regardless of previous teaching experience or progress toward licensure. Candidates with previous teaching experience demonstrated significantly greater instructional skills than candidates with no previous teaching experience. Implications and limitations discussed.